Global change witnessing the impact - Byrne, James; Gallant, george; Hutchinson-Maclcan, Laura; Gallant Production, Inc. ([S.l.] : Gallant Production, Inc. : Insight Media [distributor], 2001)
This program looks at atmospheric and biodiversity change the global warming phenomenon. Investigate the effects of pollution on various ecosystems and why the Arctic has been affected by pollution from southeast Asia, helping in understand how local activities may be affecting people on the other side of the world for years to come
Title from container
Photography, Randy Tomiuk ; editing, George Gallant, Jim mcNally ; graphics, Jim McNally
Narration: Barbara North
Keywords: Global warming; Ozone layer depletion; Climatic changes